Abiotic degradation of s-triazine pesticides analyzed by surface-enhanced Raman scattering - Rubira, R. J.G. [UNESP]; Constantino, C. J.L. [UNESP]; Otero, J. C.; Sanchez-Cortes, S. (Wiley, 2020)
In this work, we explore the use of surface-enhanced Raman scattering (SERS) on silver (Ag) nanoparticles for the detection of triazine pesticide atrazine and prometryn as well as their degradation products. This tecnique was used to monitor the pesticide degradation both in the commercial samples as well as by the effects of heat and humidity. We have studied the adsorption affinity of these pesticides as well as their degradation products on the employed SERS substrates in order to check the optimal conditions in the detection of both the original pesticide and their degradation products. The presence of these products in triazine pesticides with high solubility in water is of great interest for the human health, but what's even more important is the fact that the pesticide degradation can be favored by very mild conditions of humidity, temperature, and pH, thus leading to high levels of structural modifications, which produce other final compounds with an even higher impact on both human health and environment.
Keywords: atrazine; prometryn; surface-enhanced Raman spectroscopy; triazine dealkylation; triazine pesticides